PENGARUH E-LKPD BERBASIS MODEL PROBLEM BASED LEARNING (PBL) TERHADAP HASIL BELAJAR PEMBELAJARAN IPAS KELAS IV SEKOLAH DASAR - Kumalasari, Ika Dyah; Setiawan, Ari; Al-Masjid, Akbar; Khosiyono, Banun Havifah Cahyo (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Problem Based Learning (PBL) model on the learning outcomes of fourth-grade students in Natural Sciences and Social Sciences (IPAS) at elementary schools. The study involved 23 fourth-grade students from Sompokan Primary School. This research utilized a one-group pretest-posttest design. Student learning outcomes were obtained through pretest and posttest exams consisting of 20 short-answer questions. The pretest results showed an average score of 56.43 with a standard deviation of 12.251, while the posttest results showed improvement with an average score of 83.70 and a standard deviation of 6.071. The Kolmogorov-Smirnov test indicated that both pretest and posttest data followed a normal distribution, with significance values of 0.200 and 0.120, respectively. The correlation between pretest and posttest scores was 0.683, statistically significant (p < 0.001). Paired samples t-test showed a significant difference between pretest and posttest scores (t = -14.156, p = 0.000). These findings suggest that the use of E-LKPD based on PBL positively influences the improvement of student learning outcomes in IPAS for fourth-grade elementary school students. This method enhances interactivity and student engagement in learning, facilitating deeper understanding and critical thinking skills. Thus, E-LKPD based on PBL can be an effective strategy to enhance the quality of elementary education.